ANALISIS KUALITAS PRODUK KRIPIK SINGKONG - Paduloh Paduloh; M. Idrus Satria; Ega Jerilian (Jurnal Salome : Multidisipliner Keilmuan, 2024)
One effort to increase agricultural yields from cassava or cassava ingredients is to process them into various kinds of preparations, one of which is cassava chips. There are many MSMEs that produce cassava chips as a business, this can result in an increase in the selling value of the cassava or cassava plants. . In order for the value of sales of cassava chips to increase, it is necessary to improve the quality of the cassava chip products. The increase in cassava chips can result in increased satisfaction from consumers who buy the cassava chips product. This can ultimately have an impact in terms of increasing sales of cassava chips. Increasing sales of cassava chips can provide benefits for MSMEs and can increase the selling power of cassava sendırı or cassava chips.